2018
DOI: 10.11114/jets.v6i4a.3369
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hand, Eye, and Ear Lateralization in the Sense of Rhythm of the Athletes

Abstract: This study was carried out to investigate the relationship among the hand, eye, and ear lateralizations and the sense of rhythm of the athletes randomly selected from different sport branches.A total of 115 elite athletes including 72 males (62.6%) and 43 females (37.4%) whose mean age was 22.3±2.4 years and who receive training at different departments of the Faculty of Sports Sciences, Ataturk University were included in the study. Hand preference was assessed based on the Geschwind score by applying Edinbur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…When it is considered that hand and foot preferences can be changed through training, it is possible to say that while developing behaviors specific to a branch, not only genes but also environmental factors, training, and experiences are influential (Erhan et al, 2018). In this study, no statistically significant difference was found between heights, leg length, body weights, ages and 8 skinfold measurements in terms of hand preference of soccer players (p> 0.05).…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…When it is considered that hand and foot preferences can be changed through training, it is possible to say that while developing behaviors specific to a branch, not only genes but also environmental factors, training, and experiences are influential (Erhan et al, 2018). In this study, no statistically significant difference was found between heights, leg length, body weights, ages and 8 skinfold measurements in terms of hand preference of soccer players (p> 0.05).…”
Section: Discussioncontrasting
confidence: 52%
“…12.4% of total athletes were found to be left-handed in Cingoz et al"s (2018) study. It was reported by Erhan et al (2018) that 16.5% of the athletes were left-handed, 75.7% were right-handed and 7.8% used both hands. İmamoğlu and Kilcigil (2007) found soccer players use left foot with a rate of 16.7%, while 83.3% use right foot when they play football.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Fagard found no relationship between dominant hand and dominant eye and reading ability [ 7 ]. Erhan and Gerek investigated the relationships among the dominant hand, dominant eye, dominant ear, and exercise rhythm of athletes [ 8 ]. Witkowski et al studied the cognitive steps taken by customers when they booked a room online and the effects of website aesthetics on their booking intention [ 9 ].…”
Section: Introductionmentioning
confidence: 99%